The Association Between Clinical Characteristics and Motor Symptom Laterality in Patients With Parkinson's Disease - Zhu, Sha; Zhong, Min; Bai, Yu; Wu, Zhuang; Gu, Ruxin; Jiang, Xu; Shen, Bo; Zhu, Jun; Pan, Yang; Dong, Jingde; Xu, Pingyi; Yan, Jun; et al. (Frontiers in Neurology, 2021)
Background and purpose. The unilateral onset and persistent asymmetry of motor symptoms are important characteristics of Parkinson’s disease (PD). By using scales and wearable sensors, this study explored whether motor symptom laterality could affect non-motor symptom and gait performance. Methods. A total of 130 right-handed patients with PD were enrolled in our study and were divided into two groups according to the side of predominant motor symptom presentation by using the Unified Parkinson’s Disease Rating Scale part Ⅲ. We measured the non-motor symptoms with the Non-motor symptoms Scale, sleep quality with the Parkinson’s Disease Sleep Scale and Pittsburgh sleep quality index, cognitive function with the Mini-mental State Examination and Montreal Cognitive Assessment, quality of life with the Parkinson’s Disease Questionnaire-39, and the severity of anxiety and depression with the Hamilton Anxiety Scale and Hamilton Depression Scale, respectively. All participants underwent the instrumented stand and walk test, and gait data were collected using a set of JiBuEn gait analysis system. Results. We observed that left-dominant symptom PD patients (LPD) were associated with greater impairment of sleep quality than right-dominant symptom PD patients (RPD). We found no difference between LPD and RPD in terms of gait performance. However, compared with the severe RPD group (RPD-S), severe LPD patients (LPD-S) showed a shorter stride length and decreased range of motion of hip joints. Conclusions. In this study, LPD was associated with more sleep disturbance than RPD. In addition, LPD-S exhibited more gait impairments than RPD-S. Considering that motor symptom laterality may affect the non-motor symptom and gait performance, it should be taken into account when evaluating and treating PD patients.